Exploring Figurative Language in the Kite Runner Novel: Unveiling Semantic Depths for a Deeper Narrative Understanding - Dwi Indarti; Nabhan Ali Fikri; Marsandi Manar (Universitas Pendidikan Mandalika, 2023)
Figurative language analysis in a novel involves examining the author's use of various literary devices and techniques to enhance the narrative, evoke emotions, and create a deeper understanding of the text. This analysis goes beyond the literal interpretation of words and delves into the layers of meaning and imagery that contribute to the overall richness of the story. The purpose of this study is to seek the types of figurative language found in the novel The Kite Runner written by Khaled Hosseini and to analyze their meanings. The Kite Runner is a historical fiction novel, sets in Afghanistan in the 1970s with the social and political conditions of the Soviet invasion and the rise of the Taliban dictator. Using descriptive qualitative content analysis, this study reveals that there are 72 sentences containing figurative language and there are nine types of figurative language. Those are metaphor (15%), simile (32%), personification and, synecdoche (9%), metonymy (13%), both paradox and symbol (4%), hyperbole (7%), and apostrophe (3%). The findings show that the dominant type of figurative language in the novel The Kite Runner is simile. This study sheds light on the author of the novel The Kite Runner effective use of figurative language to enhance the narrative, convey emotions and enrich the readers’ experiences. Thus, this paper provides an in-depth analysis of figurative languages found in one of the great historical fictions.